2013
DOI: 10.2135/cropsci2012.02.0101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sorghum Genotypes Compatibility with Fusarium oxysporum under Striga Infestation

Abstract: Combined use of host resistance and Fusarium oxysporum as a biocontrol agent may provide enhanced management of Striga hermonthica (Delile) Benth. in sorghum [Sorghum bicolor (L.) Moench]. The objective of this study was to identify sorghum genotypes compatible with F. oxysporum and to determine the potential of this biocontrol agent for controlling Striga. Fifty sorghum genotypes were evaluated in the greenhouse in Striga‐infested soils with and without inoculation by F. oxysporum. A supplementary laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…The biocontrol fungus destroys Striga plants before they penetrate sorghum roots. Recent studies have indicated significant reduction in Striga numbers as well as the number of days to flowering and maturity in sorghum seeds coated with FOS (Rebeka et al, 2013;Mrema et al, 2017a). Use of FOS in Striga management in sorghum fields in East Africa is not yet reported and implemented.…”
Section: Biological Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…The biocontrol fungus destroys Striga plants before they penetrate sorghum roots. Recent studies have indicated significant reduction in Striga numbers as well as the number of days to flowering and maturity in sorghum seeds coated with FOS (Rebeka et al, 2013;Mrema et al, 2017a). Use of FOS in Striga management in sorghum fields in East Africa is not yet reported and implemented.…”
Section: Biological Controlmentioning
confidence: 99%
“…Therefore, there is a need for integrated management of the parasite through host resistance and application of FOS to enhance production and productivity of sorghum and related cereals affected by Striga.There are no reports of negative effects of FOS on sorghum or related cereal crops. In fact, FOS has been reported to promote the abundance of arbuscular mycorrhizal fungi in the rhizospheres of sorghum resulting in enhanced crop growth and development (Rebeka et al 2013;Mrema et al 2017b). Further, FOS has a very narrow host range, which is restricted to S. hermonthica, S. asiatica and S. gesneroides (Rebeka et al 2013).…”
Section: Biological Controlmentioning
confidence: 99%
See 3 more Smart Citations